Why Nigeria urgently needs to grow non-oil exports - Arndt, Channing; Adeniran, Adedeji; Chuku, Chuku; Mavrotas, George; Adetutu, Morakinyo; Ajayl, Victor (2018)
We traced the impact of the recent price declines and considered what policy options were available to the Nigerian authorities to come up with counter measures.